Bahasa Indonesia Identifikasi Pencemaran Logam Berat pada Sedimen Sungai Banda Bakali Kota Padang Berdasarkan Nilai Suseptibilitas Magnetik - Humairah, Nada Fitrati; Afdal, Afdal (Universitas Andalas, 2025)
A magnetic susceptibility analysis of sediments in the Banda Bakali River in Padang City has been conducted. Sampling was carried out at 48 points spread across the river's upstream, middle, and downstream areas at a depth of 10 cm, covering the river's left, middle, and right banks. The low-frequency magnetic susceptibility values of the samples, χlf of the sediment, ranged from 929.0×10-8 kg-1m3 to 5284.5×10-8 kg-1m3, indicating a moderate pollution level. Comparison of χlf values between river sections showed higher pollution concentrations in the riverbanks compared to the middle section. χlf values in the upstream area were relatively lower than those in the middle and downstream areas, which were influenced by increased anthropogenic activities downstream. Analysis of the superparamagnetic grain fraction based on frequency-dependent magnetic susceptibility values (χfd) indicated the dominance of magnetic particles from anthropogenic sources, mainly domestic and industrial waste. These findings confirm that magnetic susceptibility is an effective method for monitoring sediment quality and identifying the impact of human activities on heavy metal pollution in the Banda Bakali River.